2022
DOI: 10.3389/fgene.2022.840961
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Transcriptomic and Metabolomic Data to Compare the Hepatotoxicity of Neonatal and Adult Mice Exposed to Aristolochic Acid I

Abstract: Aristolochic acid (AA) is a group of structurally related compounds what have been used to treat various diseases in recent decades. Aristolochic acid I (AAI), an important ingredient, has been associated with tumorigenesis. Recently, some studies indicated that AAI could induce liver injury in mice of different age, but comprehensive mechanisms of AAI-induced differences in liver injury in various age groups have not yet been elucidated. This study aims to evaluate the causal relationship between AAI-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Additionally, Shi et al investigated the effects of sex and age on the carcinogenic capacity of AAs and found that female patients had a lower rate of renal failure due to the inhibitory effect of 17-estradiol on AAN. When exposure was prolonged, AAI caused more severe liver damage in newborn mice than in adult mice [ 16 ]. AAs not only have a high mortality rate but also accumulate in the environment and indirectly enter the human body through the food chain, leading to a range of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Shi et al investigated the effects of sex and age on the carcinogenic capacity of AAs and found that female patients had a lower rate of renal failure due to the inhibitory effect of 17-estradiol on AAN. When exposure was prolonged, AAI caused more severe liver damage in newborn mice than in adult mice [ 16 ]. AAs not only have a high mortality rate but also accumulate in the environment and indirectly enter the human body through the food chain, leading to a range of diseases.…”
Section: Introductionmentioning
confidence: 99%